Protein unties the pseudoknot: S1-mediated unfolding of RNA higher order structure. Issue 4 (13th December 2019) - Lund, Paul E; Chatterjee, Surajit; Daher, May; Walter, Nils G
Abstract: Ribosomal protein S1 plays important roles in the translation initiation step of many Escherichia coli mRNAs, particularly those with weak Shine-Dalgarno sequences or structured 5′ UTRs, in addition to a variety of cellular processes beyond the ribosome. In all cases, the RNA-binding activity of S1 is a central feature of its function. While sequence determinants of S1 affinity and many elements of the interactions of S1 with simple secondary structures are known, mechanistic details of the protein's interactions with RNAs of more complex secondary and tertiary structure are less understood. Here, we investigate the interaction of S1 with the well-characterized H-type pseudoknot of a class-I translational preQ1 riboswitch as a highly structured RNA model whose conformation and structural dynamics can be tuned by the addition of ligands of varying binding affinity, particularly preQ1, guanine, and 2, 6-diaminopurine. Combining biochemical and single molecule fluorescence approaches, we show that S1 preferentially interacts with the less folded form of the pseudoknot and promotes a dynamic, partially unfolded conformation. The ability of S1 to unfold the RNA is inversely correlated with the structural stability of the pseudoknot. These mechanistic insights delineate the scope and limitations of S1-chaperoned unfolding of structured RNAs.